Mental health mobile apps during Covid-19 Pandemic to evaluate stress level in Selangor - Zainal Abidin, Muhammad 'Adil; Rusli, Mohammad Farhan; Md Rosli, Ahmad Nabil (2022)
The COVID-19 pandemic has impacted negatively on public mental health. As a result, monitoring the level of the population mental health is a priority during crises. This study aims to measure stress during the COVID-19 pandemic in Selangor. Cross-sectional study was done using SELANGKAH apps, where users are Selangor citizens. Data was collected from September 2021 until March 2022. This app was initially used as contact tracing and mental health modules (SEHAT) were added, consisting of a validated Perceived Stress Scale (PSS-10) questionnaire. Out of 42072 SEHAT users, 6411 people had completed the questionnaire. Majority were female (53.6%), Muslims (79.6%), had formal education up to secondary (49.0%), low income (89.9%), and young and middle- aged adults (59.7%). Majority have a moderate stress (66.8%), while 23.3% and 9.9% are low and high levels, respectively. High stress is significantly associated with females, high education, younger age groups, and low monthly income. Several factors could have contributed to this throughout the COVID-19 pandemic, such as online learning, uncertainty on study duration, financial constraints and limited social interactions. Moreover, as an effect of prolonged pandemic and MCO, a surge in the number of job terminations has also affected the source of income, which contributed to high levels of stress among the general population. The level of stress in Selangor was high during the pandemic as an effect of MCO.